A Case of New Onset Cervical Dystonia in Pregnancy. Issue 1 (23rd December 2022) - Donlon, Eoghan; Moloney, Pat; Frier, Darragh; McFarlane, Robert; Smyth, Shane; Molloy, Fiona; Walsh, Richard; Lynch, Tim; McGovern, Eavan
Background: Though uncommon, primary movement disorders can occur in pregnancy, the most common being restless legs syndrome and chorea gravidarum [1 ]. New onset dystonia in pregnancy has been reported four times previously with a resolution of symptoms within six months of delivery [2 3 4 5 ]. Exacerbation of pre-existing movement disorders and the onset of de novo movement disorders during pregnancy support the hypothesis that female sex hormones play an important role in the regulation of basal ganglia circuitry. Case Report: Here we describe a case of new-onset cervical dystonia during pregnancy with persistence of symptoms after delivery. Discussion: The phenotypic overlap between this case and previously reported cases further establishes dystonia gravidarum as a distinct clinical entity.